This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Note that
3 x 2 + 6 x + 7 = 3 ( x + 1 ) 2 + 4 ≥ 4 = 2 ,
5 x 2 + 1 0 x + 1 4 = 5 ( x + 1 ) 2 + 9 ≥ 9 = 3 ,
4 − 2 x − x 2 = 5 − ( x + 1 ) 2 ≤ 5.
consequently, the left hand side of the equation ≥ 5 for any x belonging to R and the right hand side ≤ 5 for any x belonging to R. This equality is only possible under the condition that both sides of the equation are equal to 5 for the same value of x .
In this case the right hand and left hand sides are equal to only possible at x = − 1 .
Hence mod of x = 1.